Pleistocene Montane Glaciations in the Mackenzie Mountains, Northwest Territories - Duk-Rodkin, Alejandra; Hughes, Owen (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTDuring the Pleistocene the Mackenzie Mountains were affected by a series of glaciations. Through all the glaciations a single pattern seems to have been repeated: a Cordilleran ice sheet formed to the west of the continental divide and montane valley glaciers formed to the east. The montane glaciers in the Mackenzie Mountains emanated from two differents sources: a) a glacial divide, lying generally along the topographic divide between Pacific and Arctic drainage, and dividing the westerly flowing Cordilleran Ice Sheet from easterly and northerly flowing montane glaciers, b) local peaks in the Canyon Ranges. There were two well defined glacial advances in this mountain region: lllinoian, Late Wisconsinan, and one or more less defined pre-lllinoian glaciation(s). lllinoian and Late Wisconsinan glaciations are herein named Mountain River and Gayna River glaciations respectively. These advances are usually identifiable in valleys by frontal and segments of lateral moraines and glacial erosional features. Pre-lllinoian glaciation(s) have been recognized so far only in stratigraphie sections. The older advances were more extensive than the Gayna River advance; associated deposits occur higher on the valley sides and further down the valley than those associated with Gayna River Glaciation. During Mountain River Glaciation some of the montane glaciers in the Canyon Ranges merged to form piedmont glaciers. In contrast, during Gayna River Glaciation, the local glaciers consisted of single tongues, and these were mostly restricted to tributary valleys that had northward facing cirques.